Readability of Reading Texts in Student’s Handbook at The Ninth Grade of SMP Negeri 1 Telukdalam - Thomas Alfa Edison Telaumbanua; Mirsa Umiyati (International Journal of Systemic Functional Linguistics, 2019)
Readability is an indicator that used to describe whether a text more or less available to the reader level. This study attempts to find out the appropriateness of the English reading texts in terms of the readability level for the target students. This study is designed by using descriptive qualitative method. The main data used is student’s handbook. The texts were consists of 7 descriptive texts and 1 narrative text and then those data were collected by using documentary technique. In calculating readability level, the researcher employed the Flesch readability formula. The results show that the average readability level of eight reading texts was at level seven grade student by showing the average of the percentage score was 72, 96%. Then, from the eight reading texts were categorized into four levels, namely: there are 2 texts of Easy level, Fairly Easy as many as 3 texts, Standard for 1 texts, and Fairly Difficult for 2 texts. Based on the research results, it can be concluded that those texts were disagree for the target students. Thus, for teachers, English Teacher particularly, should be wise in choosing a textbook as material for teaching students must be match with their capabilities level.